பேராசிரியர் நூல்களில் அணிந்துரைகள் / Foreword in the Texts Written by Professor - முனைவர் சி. அருள் செல்வம் / Dr. S. Arul Selvam (International Journal of Tamil Language and Literary Studies, 2022)
‘Agathin Alagu Mugathil theriyum’ is a classic proberb. According to Nannular, it is not an exaggeration to say that what one wears is a smile, inner beauty, a gentle face, and the foreword is also like that for a book. A foreword of the book is the glory of the book and explains about the book in a precise manner, That is, it introduces the book to everyone and enables them an opportunity to know the essence of the book. It gives an understanding of the book and not a criticism or praise written about the book. Before writing a foreword for a book, the main thing to be noted is the personality of the reviewers for that book. V. Subha Manikanar, who had written a foreword to Professor N. Subburettiyar's book “Agathinai Kolgaigal” (Inner Principles), says that the reason for his work was that he knew about the indepth knowledge of professor’s scientific thinking. That is, the main purpose of the foreword and it introduces the book to everyone and giving them an opportunity to know the essence of the book in a clear manner. This article examines the merits of the forewords written by most respected scholars including the former Vice-Chancellor Madurai Kamaraj University, Prof. V. Subha Manickam to great writers such as Avvai Natarasan, Kamban Adisoodi Phala. Pahalaniappan (student of Professor N.Subburettiyar) to the classic works of N. Subbu Reddiar.